Emotional stress estimation in general population - Altaf, Maria; Noushad , Shamoon; Ahmed , Sadaf; Azher, Syed Zain; Shaikh Muhammad Tariq (International Journal of Endorsing Health Science Research, 2014)
Despite great deal of popular research interest in existence and altered body responses of emotional stress there are still strong arguments regarding its positive and negative impact on psychophysiological health. Stress is a state of mental or emotional strain or suspense and also a number of normal reactions of the body (mental, emotional, and physiological) and designed for self-preservation. The potentially lethal consequences of emotional stress are deeply rooted in folk wisdom, as reflected by phrases such as scared to death and a broken heart. In the past decade, cardiac contractile abnormalities and heart failure have been reported after acute emotional stress. A cross sectional study, data was collected by means of structured questionnaire from 370 subjects (age ranges between 20-50 years). Stress was accessed by using Sadaf Stress Scale (SSS) which comprises of 114 items divided into seven subscales data was analyzed by using SPSS 20.0. The main findings of this study are that emotional stress has a direct relation with age. People ranging below 30 years showed emotional stress and women being remarkably more susceptible to it.